The Drosophila mitotic spindle orientation machinery requires activation, not just localization. - Neville, K.E.; Finegan, T.M.; Lowe, N.; Bellomio, P.M.; Na, D.; Bergstralh, D.T. (EMBO Reports, 2023)
The orientation of the mitotic spindle at metaphase determines the placement of the daughter cells. Spindle orientation in animals typically relies on an evolutionarily conserved biological machine comprised of at least four proteins - called Pins, G?i, Mud, and Dynein in flies - that exerts a pulling force on astral microtubules and reels the spindle into alignment. The canonical model for spindle orientation holds that the direction of pulling is determined by asymmetric placement of this machinery at the cell cortex. In most cell types, this placement is thought to be mediated by Pins, and a substantial body of literature is therefore devoted to identifying polarized cues that govern localized cortical enrichment of Pins. In this study we revisit the canonical model and find that it is incomplete. Spindle orientation in the Drosophila follicular epithelium and embryonic ectoderm requires not only Pins localization but also direct interaction between Pins and the multifunctional protein Discs large. This requirement can be over-ridden by interaction with another Pins interacting protein, Inscuteable.